Pencemaran Nama Baik Melalui Media Sosial Berdasarkan Putusan Nomor 26/PID.SUS/2022/PT SBY - Dani, Rendy Arsa Alvian (Jurnal Ilmiah Wahana Pendidikan, 2024)
Defamation through technological sophistication in the form of software, or better known as defamation through social media. This crime can also be included in cybercrime, it is regulated in article 27 paragraph (3) of Law No. 11 of 2008 concerning information and electronic transactions and in the Criminal Code. In determining the decision related to defamation through social media, it must meet the elements in a defamation case on social media. So that the judge in deciding case number 26 / PID. SUS/2022/PT SBY must meet these elements. The research was carried out using a normative juridical approach and the specifications were carried out using a descriptive analysis. Sources and types of data used are primary data, secondary data and tertiary data. Data collection techniques using interview techniques and literature study, and the data obtained will be analyzed descriptively qualitatively. The results of the study can be concluded that Indonesian legal arrangements regarding online shop fraud crimes can be seen in Article 378 of the Criminal Code and Law Number 11 of 2008 concerning Information and Electronic Transactions which in its implementation the ITE Law does not yet contain articles that specifically act criminal defamation, Article 27 (3) of the ITE Law which focuses on the act of spreading false and misleading news that harms people or institutions. Because this criminal act of defamation is a cyber crime, the proof must use electronic evidence or electronic documents or printouts based on the provisions of Article 5 of the ITE Law.